Balsa wood derived condensed, heteropore-connected 3D carbon– sojourn from herbal, non-hazardous stuff to flexible energy-storage device. (February 2021) - Duan, Yongtao; Kashif, Muhammad; Dhar, Abhishek; Vekariya, Rohit L.; Sangani, Chetan B.; Bhadja, Poonam; Muddassir, Mohd.
Highlights: Balsa wood derived highly interconnected 3D porous carbon used as electrode material for flexible supercapacitor (FSC) MnO2 doped biomorphic carbide (Bio-C/MnO2) shows excellent porosity and electrochemical performance Bio-C/MnO2 composite based FSC had a specific capacitance of 148 F.g−1 and 78.77% capacitance retention after 10000 cycles. Abstract: The biomorphic carbide (Bio-C) with highly interconnected pore-joined carbon structure consisting of three dimensional alignments was prepared based on balsa wood, a non-hazardous herbal stuff, resulting an economic, environment-friendly fabrication process. The balsa wood gives hierarchical natural porous structure after the hydrothermal process, which offers ample enlargement area for MnO2 and eliminates the aggregation of MnO2 particles. Evolution of structure, morphology, and porous properties from pristine carbonized wood to porous Bio-C/MnO2 was systematically studied. The electrochemical performance of the Bio-C/MnO2 composite has been studied in a flexible symmetric supercapacitor (FSC) using PVA/H2 SO4 hydrogel as an electrolyte. The as-prepared Bio-C/MnO2 composite demonstrated staggering electrochemical output, which is majorly resulted due to the large amount of pore volume along with 3D hierarchical pores. Electrochemical study showed that the Bio-C/MnO2 composites used in FSC had a specific capacitance (sp. cap.) of 148 F.g −1 at current density of 0.8 A.g −1, and exhibited stable long cycle life with a capacitance retention ratio of 78.77 % after 10000 cycles. The Bio-C/MnO2 hybrid materials having three dimensional porous structures are excellent materials in the wide area of bendable power storage system. Graphical abstract: Image, graphical abstract